Myriapoda at 'Reserva Ducke', Central Amazonia/Brazil - Adis, Joachim (2002)
Myriapoda contains the four recent classes Chilopoda, Diplopoda, Pauropoda and Symphyla. In total, 159 families, 2166 genera and >15162 species are known world-wide Twenty-nine families, >93 genera and >401 described species occur in Amazonia. One-fifth of the families presently known in the myriapods are represented in Amazonia. About 3% of all described species live, and at least 9% of the species estimated to exist world-wide in Myriapoda are assumed to live in Amazonia. From the forest reserve ‘Reserva Ducke' near Manaus, 22 families, 38 genera and 73 described species are known at present. The Chilopoda represent 5 families, 9 genera. 23 species and one undcscribcd morphospecies, the Diplopoda 13 families, 18 described genera. 14 species and 19 undescribed morphospecies, the Pauropoda 2 families, 7 genera. 31 species, and the Svmpyla 2 families, 4 genera and 5 species. All names are listed.